Addressing National Needs: Design Thinking-Driven Engineering of a Multi-Purpose Logistics Vehicle for Indonesia's Free Nutritious Meals (MBG) Program - Indra Candra Setiawan; Muji Setiyo; Muhammad Latifur Rochman (Automotive Experiences, 2026)
Indonesia's Free Nutritious Meals Program (MBG), launched in January 2025, aims to deliver daily meals to up to 80 million beneficiaries but faces persistent logistical challenges related to geographic dispersion, vehicle limitations, and food safety risks. Conventional delivery vehicles are often incompatible with Indonesia's diverse terrain, resulting in inefficiencies, food spoilage, and service delays. Therefore, this article advances an evidence-based design argument that positions Design Thinking, augmented by Kansei Engineering principles, as a practical design logic for addressing these nationally significant challenges through real-world vehicle adaptation. Grounded in stakeholder engagement, field observation, and iterative prototyping, a Toyota GUN125-based multi-purpose logistics vehicle was developed to support end-to-end MBG meal distribution. Key design interventions include a reconfigurable rear cabin with a three-way door system, a dedicated food trolley, reinforced suspension, and ergonomically optimized loading and unloading mechanisms. These features were derived from operational pain points and translated into engineering solutions through an iterative Design Thinking process. Field validation along a 25 km distribution route provides empirical support for the proposed design. Performance evidence indicates 98.7% operational uptime, zero thermal breaches, food waste reduced to 2% from a 28% baseline, and a 42% reduction in delivery cycle time from 5.5 hours to 3.2 hours. The vehicle configuration supports a distribution capacity of up to 612 meals per school and achieved Kansei post-test scores averaging 4.6 out of 5 for reliability and user-friendliness. The integrated evidence demonstrates how user-centered automotive engineering, grounded in operational realities, can enhance public service logistics performance. The proposed vehicle concept offers a scalable and locally adaptable platform aligned with MBG objectives and provides a transferable design perspective for other perishable goods distribution systems.